Fostering Students' English Grammar Learning Outcomes and Handling Classroom Technological Inclusivity by Integrating Quizizz Paper Mode - Fadhilawati, Dian; Fauzi, Adin; Mansur, Moh; Rachmawati, Dwita Laksmita (Lingual Journal of Language and Culture; Vol 17 No 1 (2024): Lingual: Journal of Language and Culture, 2024)
This study embarked on fostering grammar learning outcomes of tenth-grade students at MAN Kota Blitar and handling classroom technological inclusivity by integrating Quizizz paper mode as a pedagogical tool in teaching Simple Past and Present Perfect Tenses. This study utilized four stages of classroom action research, encompassing planning, implementation, observation and evaluation, and reflection. The researchers used pre-tests, post-tests, and questionnaires for collecting the data. The outcomes unveiled a substantial improvement in students' grammatical learning outcomes, from 66.50 in the pre-test to 89.50 in the post-test. Further, students displayed favorable reactions, affirming the power of Quizizz paper mode in addressing challenges in grammar learning due to its engaging nature, cost-effectiveness, and provision of real-time feedback. Additionally, it fosters inclusivity by allowing every student to participate, irrespective of their access to technology. Moreover, it offers students a chance to rest their eyes and electronic devices while combining physical and digital learning experiences. The findings of this study suggest that integrating technology-based platforms like Quizizz in paper mode can enhance grammar mastery by promoting increased engagement and interactivity among students. Based on those results, it is recommended that future researchers explore Quizizz paper mode for teaching various grammar topics or language skills studies by applying larger sample sizes and examining the prolonged effects of utilizing Quizizz paper mode on students' mastery of grammar or other English sub-skills.